Truncated Inverse Generalized Rayleigh Distribution and Some Properties - Kalaf, Bayda atiya; Abdul Ameer Jabar , Noor; Madaki, Umar Yusuf (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Truncated distributions arise naturally in many practical situations. It’s a conditional distribution that develops when the parent distribution’s domain is constrained to a smaller area. The distribution of a right truncated is one of the types of a single truncated that is restricted within a specific field and usually occurs when the specified period for the study is complete. Hence, this paper introduces Right Truncated Inverse Generalized Rayleigh Distribution (RTIGRD) with two parameters is introduced. Then, provided some properties such as; (probability density function, cumulative distribution function (CDF), survival function, hazard function, ‎rth moment, mean, variance, Moment Generating Function, Skewness, kurtosis, Median, and Mode for Right Truncated Inverse Generalized Rayleigh Distribution on [0,1].